Role of Parathyroid Hormone Assay and Bedside Ultrasound in the Emergency Department in Differentiating Acute Kidney Injury from Chronic Kidney Disease: A Systematic Review - Deepali Junnarkar Roy; Shrikant Digambarrao Pande; Zhong Hong Liew; Debajyoti Roy (Emergency Medicine International)
Introduction. It is not uncommon for patients without preceding history of kidney disease to present to the Emergency department with renal failure. The absence of prior medical records or renal imaging presents a diagnostic challenge. Elevated parathyroid hormone levels or echogenic contracted kidneys on ultrasound are known to point to a diagnosis of chronic kidney disease. The literature in this regard is surprisingly limited. The objective of this study is to assess the role of intact parathyroid (iPTH) blood level and bedside ultrasound in differentiating acute kidney injury from chronic kidney disease. Methods. A systematic review which included a literature search of 3 databases, PubMed, Embase, and Cinahl (R) as also secondary sources, was done. The inclusion criteria evaluated studies which evaluated iPTH or bedside ultrasound in differentiating acute kidney injury from chronic kidney disease. We excluded studies which used other laboratory biomarkers like neutrophil gelatin associated lipocalin (NGAL) or carbamylated haemoglobin. A total of 2256 articles were identified. After screening, the relevant articles were reviewed, and an assessment of their methodological quality was made based on the CASP: Critical Appraisals Skill Programme. Results. Of the 2256 articles identified, after screening, only 5 were identified as relevant. Conclusions. An elevated parathyroid hormone level and echogenic contracted kidneys on bedside ultrasound in the Emergency department can help differentiate acute kidney injury from chronic kidney disease. This differentiation helps decide need for admission as well as further management. Although iPTH level may also rise in acute kidney injury, the value (2.5 times normal) can discriminate it from chronic kidney disease.